“Nobody cares, lah!” the phenomenon of flaming on YouTube in Malaysia - Lingam, Revathy Amadera; Aripin, Norizah (Center for Sustainabality Research & Consultancy, 2016)
Objective: The purpose of this paper is to investigate what motivates people to provide malicious comments on YouTube in Malaysia. This study will also question the differences between how flaming is constructed in each video classification and how are flaming comments categorized. Methodology: This study uses qualitative methods.Literature review has been summarized to contextualize the research problem. Findings: The paper offers rich theoretical insights to understand the practical issue of ridiculous comments by internet users on YouTube. Implications: Flaming or making ridiculous comments on social media has been a serious issue in Malaysia and other countries with high internet usage.Findings of the study will help understand the views of YouTube community in Malaysia on flaming. The study may further help understand the issue of flaming on other social media sites.